SECURITY CHALLENGES IN AI-DRIVEN CHATTING WEBSITES - Ismoil Sapayev Anvar oglu (PEDAGOGS, 2025)
Abstract: AI-driven chatting websites are increasingly used in customer service, education, and personal assistance. While these platforms offer efficiency and user engagement, they also introduce significant security risks. Issues such as data privacy, unauthorized access, injection attacks, and misuse of AI-generated content pose challenges for developers and users alike. This article discusses the primary security concerns related to AI-enabled chat systems, with a particular focus on web applications built with PHP. It also provides recommendations for creating secure, reliable, and trustworthy chatbot platforms that balance innovation with user protection.